2015
DOI: 10.1021/acs.jafc.5b03482
|View full text |Cite
|
Sign up to set email alerts
|

Tangeretin from Citrus reticulate Inhibits Respiratory Syncytial Virus Replication and Associated Inflammation in Vivo

Abstract: Human respiratory syncytial virus (RSV) is a common pathogen that causes pneumonia and bronchiolitis in infants and young children. Our previous study showed that tangeretin from Citrus reticulate possessed potent in vitro anti-RSV effects comparable to that of ribavirin. Therefore, in this study, we investigated the in vivo anti-RSV activity of tangeretin in 3-week-old male BALB/c mice. A plaque reduction assay and fluorescence quantitative polymerase chain reaction (FQ-PCR) showed that tangeretin inhibited R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Interestingly, the two most abundant polymethoxylated flavones identified in the extract of "Guangchenpi", tangeretin and nobiletin, determined a dose-dependent inhibition of the virus, calculated by plaque reduction assay. The same authors have subsequently investigated the activity of tangeretin from C. reticulata in vivo using 3-week-old male BALB/c mice [94]. As previously shown in vitro, the results from this study confirmed an inhibition of the RSV replication exerted by tangeretin in the lung of the mice.…”
Section: Antimicrobial and Antiviral Effect Of Citrus Flavonessupporting
confidence: 81%
“…Interestingly, the two most abundant polymethoxylated flavones identified in the extract of "Guangchenpi", tangeretin and nobiletin, determined a dose-dependent inhibition of the virus, calculated by plaque reduction assay. The same authors have subsequently investigated the activity of tangeretin from C. reticulata in vivo using 3-week-old male BALB/c mice [94]. As previously shown in vitro, the results from this study confirmed an inhibition of the RSV replication exerted by tangeretin in the lung of the mice.…”
Section: Antimicrobial and Antiviral Effect Of Citrus Flavonessupporting
confidence: 81%
“…Hesperidin was found to be the most predominant flavonoid in tangerine peel, followed by tangeretin and nobiletin (Ho and Kuo, 2014). Even though pharmacological activity such as neuroinflammatory activity, antibacterial, antifungal, antiaging, anti-tyrosinase, anti-acne, antiallergic, anticancer, anti-inflammatory and antiviral activity against the human respiratory syncytial virus (RSV) have been assigned to these compounds, it is known that these compounds individually often do not account for the activity of the extracts, and that these compounds in combination is responsible for the pharmacological activities observed (Kim et al, 2008a;Ho and Kuo, 2014;Rashed et al, 2015;Xu et al, 2015;Vargas et al, 2016;Adhikari et al, 2017;Hagenlocher et al, 2017). Additionally tangeretin and nobiletin also showed the best antibacterial activity against Staphylococcus aureus, Microsporum canis, Escherichia coli, Trichophyton mentagrophytes when tested against bacterial and fungal species when the peel extracts of C. sinensis, C. limon, and C. reticulata were tested, with antimicrobial activity also reported for these compounds in the leaf extract of C. volkameriana (Johann et al, 2007;Rashed et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The minimal concentration required to inhibit 50% of plaques (IC 50 ) was calculated by regression analysis of the doseresponse curve generated from the data. The cytotoxicity of the compounds was determined in cultures of HEp-2 cells using the MTT method (25). The assays were carried out in triplicate and the results were from 3 independent experiments.…”
Section: Plaque Assaymentioning
confidence: 99%